Localising and translating museums: a comparative investigation of museum websites - Li, Lu (2024)
A museum is an organisation where culture, history and ideas are presented, interpreted, and promoted. Museum texts as essential communicative tool and their translation have been investigated for decades as to how to make knowledge intelligible to visitors. Despite museum websites playing increasingly important roles in presenting and interpreting culture, they receive comparatively little attention and have remained largely unexplored and under-researched in the area of website translation research and localisation industry. During and after the global Covid-19 pandemic, museums have increasingly relied on website in an attempt to continually engage with visitors. Their design, as a result, have generally become more varied to engage with users online. This thesis investigates museum websites with regards to the ways in which they represent themselves as well as the cultures and values they stand for. By studying the Chinese-to-English translations of the homepages and exhibition webpages of three museum websites, this thesis explores how these are translated and reshaped for different target audiences. The study explores the museum websites from a multimodal perspective and examine them using an extended model based on Ravelli’s (2006) communicative frameworks for museum to analyse the representational, interactional and organisational meanings made and reshaped on the three websites in both the Chinese and English versions. The aim involves exploring a) the way visuals and verbals are used on the websites for meanings (re)making when it comes to communicating with different home and international users; b) the strategies and techniques adopted to localise and translate a museum website, and c) the effects of those strategies and techniques. To study the three aspects, a three-stage method is established for the three case studies. It is drawn from a framework integrating theoretical concepts from Systematic Functional Theory to complement Ravelli’s communicative framework. Finally, the thesis propounds the rationale behind the selected cases’ different strategies of website localisation and translation by looking beyond their online presence to the possible influence of the social factors. The inclusion of it is in reference to a museum’s social function in general. Finally, the thesis aims to draw attention to the unique nature of museum website translation, which should be considered separately from commercial websites.